Interventional Management of Vertebral Body Metastases - Prince, Ethan A.; Ahn, Sun Ho (Seminars in Interventional Radiology, 2013)
Metastases to the vertebral column are often due to hypervascular primary tumors, the most common of which is renal cell carcinoma. Clinical symptoms attributed to vertebral body metastases include localized pain, mechanical instability of the vertebral column, and neurologic deficits resulting from mass effect. Treatment options include targeted radiotherapy, percutaneous vertebral augmentation with or without thermal ablation, and surgical resection with subsequent fusion. Overall, surgical resection of the tumor and stabilization of the vertebral column provide the best prognosis for the patient in terms of symptomatic improvement and long-term survival; however, resection of hypervascular vertebral body metastases can result in significant intraoperative blood loss that can add to the morbidity of the procedure. Preoperative embolization of hypervascular metastases of the vertebral column has been shown to significantly reduce intraoperative blood loss at the time of surgery. The goal of this manuscript is to describe the role of embolization therapy in the management of patients with vertebral body metastases.
Keywords: vertebral body; metastasis; embolization; ablation; interventional radiology